FACTORS AFFECTING POTATO LATE BLIGHT DEVELOPMENT IN PUNJAB - C. D. RAVINDRAN, O. M. BAMBAWALE, S. K. BHATTACHARYYA AND (Indian Phytopathology, 2002)
Factors responsible for onset of late blight in sub-tropical Punjab were different from those considered necessary under the temperate, long-day crop-growth. Out of the 10 biometeorological variables considered, only hours temperature> 20°C consistently correlated negatively with disease progress. In moderate 1982 epidemic, rain (mm) and hours temperature> 20°C and, in the severe 1985 epidemic, hours temperature < lOoC and hours temperature> 20°C were important variables in late blight progress through their high, positive/negative, direct effects. RH > 80 and 90 per cent, cloudy days and age of plants significantly correlated with disease progress in 1982 and 1985 but were not directly responsible. The disease could develop rapidly even in total absence of rains and dew appeared to be the alternative source of free moisture. Factors affecting inoculum survival during early crop growth stages seem crucial in deciding late blight behaviour in a season.